The Phenomenon of Mitigation in The Contemporary Hail Dialect, a Lexicon of (Fasih Al-‘Ami in The North of Najd by ‘Abd Al-Rahman Al-Suwayda’) as a Model: LEXICOLOGY - Fahd Salem Muhammad Magloth, (Al-Ḍād Journal, 2022)
Deletion is one of the most important means of mitigation in the Ha’il dialects, and the hamza in the Ha’il dialects is permissible in which three rulings are permitted: it be reduced, omitted, or replaced by Ya. Most of the deletion of the mitigation in the Ha’il dialects goes as far as deleting the hamza; Because it is from the extreme of the throat, and it is one of the strongest letters, and the substitution of the hamza ya or wawa in the chapter of mitigation is the second level of mitigation in the Ha’il dialects. The research revealed the confusion between the deletion of the hamza and its reduction in the lexicon (Faseh al-Ami in the north of Najd by Abd al-Rahman al-Suwayda). Aspects of mitigation appeared in the Ha’il dialect in five ways: 1- Deletion 2- Reducing the hamza 3- Facilitating the hamza 4- Substitution of a letter with a weaker letter such as ya and waw 5- Expansion of use in the spatial heart section 6- Elimination of convergence of homologous in the chapter on immersion 7- Substitution of a letter of the gender of another letter in the chapter on the heart The slur. This research proceeds according to the descriptive approach, which is based on the analysis of texts in the Hail region. Through the research, objectives emerged, including highlighting the cultural product of Hail, the most prominent linguistic shifts in it, and the reasons for that; And standing on the linguistic and cultural phenomena as a tributary of the tributaries that contribute to the realization of the vision of the Kingdom of Saudi Arabia 2030.